2021
DOI: 10.3390/ma14164415
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Structure and Properties of Two-Phase Ti-6Al-4V Alloy during Cold Metal Transfer Additive Deposition with Interpass Forging

Abstract: The paper deals with the main formation patterns of structure and properties of a titanium alloy of the Ti-6Al-4V system during additive manufacturing using cold metal transfer (CMT) wire deposition. The work aims to find the optimal conditions for layer-by-layer deposition, which provides the high physical and mechanical properties of the titanium alloy of the Ti-6Al-4V system hybrid, additively manufactured using CMT deposition. Particular attention is paid to interpass forging during the layered printing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The peak in the β phase in all three samples did not change significantly. This indicated that the β phase was uniformly distributed along the radial direction of the wheel hub [ 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The peak in the β phase in all three samples did not change significantly. This indicated that the β phase was uniformly distributed along the radial direction of the wheel hub [ 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Refs. [ 42 , 43 , 44 ] stated that alloys with a lamellar microstructure exhibit an improved strength due to modifications in the crack direction and the appearance of secondary crack branching. Figure 9 a shows that modifying the crack path along the α/β phase boundary in a lamellar structure changes the crack propagation direction.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown in [16][17][18], using several alloys as examples, that the use of layer-by-layer peening during the additive manufacturing of a workpiece reduces stresses, decreases grain size and, as a consequence, increases the mechanical characteristics to the level of the basic metal, reduces the metal's porosity and anisotropy. In the article [19] there was also shown a significant decrease in the anisotropy of the mechanical properties when layer-by-layer shot peening was applied. This approach was used in the present study during the wire plasma deposition welding of workpieces from the 308LSi austenitic steel.…”
Section: Introductionmentioning
confidence: 96%